TEORI NASIKH MANSUKH DAN RELEVANSINYA DENGAN REVISI UNDANG-UNDANG KOMISI PEMBERANTASAN KORUPSI (KPK) - Rambe, Laila Afni (Institut PTIQ Jakarta, 2022)
The concept of nasikh mansukh is used to analyze the conflicting legal meaning of a verse of the Qur'an. So that it is understood that nasikh mansukh is one way to look at the sociological, philosophical and even economic background of a verse of the Qur'an revealed by God. Seeing this it seems difficult to match the use of law in the time of the prophet with what is happening in the present. Because the times are always moving dynamically. But the way to deny a verse in a country has in common is the revision of the law. The purpose of this research is to see how the use of the concept of nasikh mansukh when brought into the realm of state administration. From the results of the analysis conducted by the author on the data, it can be concluded that in essence there is no contradiction in the verses of the Qur'an but each of the verses is perfect for each other, meaning that there is always a connection if our understanding is universal towards the verses of the Qur'an. Furthermore, when alluded to the nasikh mansukh in the realm of constitutionality there is a close relationship with the meaning of the revision of the law. This can be seen from the terms of nasikh mansukh which then have in common with the provisions of the revision of the law